2005
DOI: 10.1038/sj.mp.4001671
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms during childhood and adult obesity: the Zurich Cohort Study

Abstract: Depression and obesity have become major health problems with increasing prevalence. Given the limited effectiveness of treatment for weight problems, the identification of novel, potentially modifiable risk factors may provide insights on new preventive approaches to obesity. The purpose of this study was to test the hypothesis that depressive symptoms during childhood are associated with weight gain and obesity during young adulthood. Participants were from a prospective community-based cohort study of young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
3
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 45 publications
(64 reference statements)
9
146
3
5
Order By: Relevance
“…Recent epidemiological studies suggest relatively strong longitudinal associations between depressive symptoms during childhood and adolescence and the development of later obesity in women. 13,14 The current study adds to previous reports that childhood depressive symptoms may also explain some of the asthma-obesity comorbidity.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Recent epidemiological studies suggest relatively strong longitudinal associations between depressive symptoms during childhood and adolescence and the development of later obesity in women. 13,14 The current study adds to previous reports that childhood depressive symptoms may also explain some of the asthma-obesity comorbidity.…”
Section: Discussionsupporting
confidence: 53%
“…31 Neither of these studies reported data on the incidence of asthma after weight gain. The observation that important increases in fat mass emerge later in men than in women 13,31 may explain some inconsistent gender differences in the asthma-obesity association.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations